Impact of suppressive antiviral therapy on the health related quality of life of patients with recurrent genital herpes infection. Issue 6 (1st December 1999) - Patel, R; Tyring, S; Strand, A; Price, M J; Grant, D M
Abstract : OBJECTIVE: To investigate whether suppressive antiviral therapy improves health related quality of life in patients with recurrent genital herpes. METHODS: Health related quality of life was measured using the disease specific recurrent genital herpes quality of life questionnaire (RGHQoL) as part of a randomized, double blind, 52 week, placebo controlled, dose ranging study of once and twice daily valaciclovir or aciclovir for the suppression of recurrent genital herpes in patients with six or more recurrences per year. RESULTS: Of 1479 participants, 1349 patients completed the baseline questionnaire. There were no significant baseline differences in RGHQoL score between any of the treatment groups. After 3 months there were significantly greater improvements in mean RGHQoL scores for all active treatment groups compared with placebo (p < 0.05). Mean RGHQoL score improvements from baseline remained significantly higher in the active treatment groups than in the placebo group after 6 and 12 months, indicating that the improved health related quality of life in patients receiving suppressive antiviral therapy was sustained over a prolonged period of time. CONCLUSION: Suppressive antiviral therapy is an effective strategy for improving the quality of life of patients with recurrent genital herpes. These improvements in quality of life are sustained over time, thus enhancing the clinical benefit in the long term management of this condition.